THE IMPORTANCE OF LUDIC: SINGING GAMES IN FACE OF EARLY CHILD EDUCATION/A IMPORTÂNCIA DO LÚDICO: BRINCADEIRAS CANTADAS EM FACE DE EDUCAÇÃO INFANTIL (Fiep Bulletin - online, 2019)
This article aims to contribute to the enrichment of teaching-learning by the playful and music amplifying and enrichingthe knowledge of the teacher and student. Likewise, in the perspective of a more in-depth knowledge about the history of the useof the ludic in its daily ones in the schools. In this research also rescued the importance of the origin of the lúdico in the World and in Brazil, until the present day. The importance of the play as a methodological instrument is approached from the point of view ofthe use of the same in the search for a better learning of the students, in relation to the jokes and songs inserted and used inschools. Thus, there is an interrelation starting from the choice of the best play activity to be used for each programmatic contentand we want to develop the cognitive, affective and motor side of our students, in order to favor the exploration of the potential andthe development of the abilities that they provide. The exploratory and descriptive methodology described the visits were made inthe period from February 2017 until May 2018. The project was carried out in the schools of Belém do Pará and extended to theindigenous Warao communities of Venezuela that are in Belém, totaling 8,400 students attended. We conclude in the result thatverified several authors defend the use of the playful with the students in the schools directly aid in the disciplinary improvement,attendance, responsibility and attention, thus, with greater commitment of the teachers to work with jokes and songs, besidesworking the cognitive part of children is memorization.
Keywords: Ludic; Teaching-learning; Educator; Games; Students